2015
DOI: 10.1074/mcp.m115.051151
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Proteome of Mycobacterium tuberculosis during Dormancy and Reactivation

Abstract: Tuberculosis, caused by Mycobacterium tuberculosis, still remains a major global health problem. The main obstacle in eradicating this disease is the ability of this pathogen to remain dormant in macrophages, and then reactivate later under immuno-compromised conditions. The physiology of hypoxic nonreplicating M. tuberculosis is well-studied using many in vitro dormancy models. However, the physiological changes that take place during the shift from dormancy to aerobic growth (reactivation) have rarely been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(123 citation statements)
references
References 72 publications
5
117
1
Order By: Relevance
“…For inducing hypoxia, MTB was grown in an in vitro dormancy model as described by Gopinath et al . . Briefly, log phase MTB culture grown in Dubos medium (Difco) was transferred to glass tubes at a head space ratio of 0.6.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For inducing hypoxia, MTB was grown in an in vitro dormancy model as described by Gopinath et al . . Briefly, log phase MTB culture grown in Dubos medium (Difco) was transferred to glass tubes at a head space ratio of 0.6.…”
Section: Methodsmentioning
confidence: 99%
“…Dormancy was induced as reported by Gopinath et al . . DNA·protein crosslinking was carried out by the addition of formaldehyde to a final concentration of 1% to 20 mL of the bacterial culture, and incubated at 25 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Because the number of spectral counts correlates with the abundance of the protein, the method can be used to compare protein abundances between biological samples that are prepared and processed in parallel (29)(30)(31). This method is widely accepted in the proteomics community and has been used to identify differences in protein levels in Shewanella oneidensis grown under oxic and anoxic conditions (32), the relative levels of 3,274 mouse proteins in the brain, heart, kidney, liver, lung, and placenta (28), and changes in protein levels in Mycobacterium tuberculosis during reactivation from a dormant state (33). We found that M3 results in a 2-fold increase in the level of ProA*, whereas the level of ProB is unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…Immunization, serum collection, antibody purification and western blot against MTB cell-free extract were carried out as described by Gopinath et al [16]. All the guidelines of the Institute Animal Ethics Committee, Rajiv Gandhi Centre for Biotechnology, were followed for animal handling.…”
Section: Antibody Preparationmentioning
confidence: 99%
“…RNA isolation, cDNA synthesis and quantitative PCR RNA isolation from MTB was performed following Gopinath et al [16] using Trizol (Sigma-Aldrich) reagent. The RNA preparation was resuspended in nuclease-free water and treated with DNaseI (Sigma-Aldrich) at room temperature for 30 min.…”
Section: Reporter Constructs and Spectrofluorimetrymentioning
confidence: 99%